STUDY OF LEAKAGE CURRENT AND THERMAL BEHAVIOR ON CORRODED 150 KV CERAMIC INSULATORS (CASE STUDY GOMBONG-RAWALO-KESUGIHAN LINE) - Aulia Nissa Adjie, Leavinindya
The reliability of the electric power transmission and distribution system is related directly to the performance of the insulator. The insulators work as a high voltage isolation by withstanding the electric field, and separate a high voltage conductors from its towers. The insulators that are installed on transmission and distribution lines have a risk of corrosion occurring on iron caps or steel pins. Corrosion is influenced by environmental factors such as pollution, air humidity, and fog thickness. The impact of corrosion on insulators can be observed from the electrical aspect and thermal behavior aspect that affect the performance of the insulator itself. This study used 150 kV ceramic insulators which had stopped operating on Gombong-Rawalo-Kesugihan route due to corrosion as a samples. The electrical parameters test containing observation of magnitude and waveform of the leakage current, as well as the THD. Leakage current tests were carried out in dry clean and salt fog conditions which created from the evaporation of seawater from Teluk Penyu. The thermal behavior was observed using a thermal camera focusing on steel pin where the corrosion was most severe. The leakage current test shows that leakage current detected will increase as the severity level of corrosion. The result of thermal test showed that the average temperature at the insulators pin increase significantly along with the severity of the corrosion.